2011
DOI: 10.1007/s12664-011-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Helicobacter pylori infection protect against esophageal diseases in Asia?

Abstract: The speculations on the protective role of Helicobacter pylori against gastroesophageal reflux disease (GERD) originated from epidemiological observations. These studies have shown that the rising trend of GERD is coincident with declining prevalence of H. pylori and peptic ulcer disease in Asia. Furthermore, most case-control and population-based studies suggest a negative association between H. pylori infection and GERD. It is generally believed that the preponderance of cagA+ and vacA+ virulent strains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Patients who underwent H. pylori eradication treatment in our department between 2008 and 2013 and in whom H. pylori was successfully eradicated were enrolled in this study. A 13 C-urea breath test result of 2.5‰ or less (Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan), or negative result on the stool H. pylori antigen test 6 weeks after the end of eradication treatment (SRL, Inc., Tokyo, Japan) was considered as successful eradication of H. pylori. Inclusion criteria were the following: patients who underwent endoscopy within 1 year before the start of eradication treatment and had images of the gastroesophageal junction that could be used to determine the presence or absence of RE, and who underwent endoscopy 3 years or more than 3 years after eradication treatment and had the same images as those described above.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who underwent H. pylori eradication treatment in our department between 2008 and 2013 and in whom H. pylori was successfully eradicated were enrolled in this study. A 13 C-urea breath test result of 2.5‰ or less (Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan), or negative result on the stool H. pylori antigen test 6 weeks after the end of eradication treatment (SRL, Inc., Tokyo, Japan) was considered as successful eradication of H. pylori. Inclusion criteria were the following: patients who underwent endoscopy within 1 year before the start of eradication treatment and had images of the gastroesophageal junction that could be used to determine the presence or absence of RE, and who underwent endoscopy 3 years or more than 3 years after eradication treatment and had the same images as those described above.…”
Section: Subjectsmentioning
confidence: 99%
“… 9 , 10 The gastric acid secretion capacity of H. pylori -infected persons is often lower than that of uninfected persons, and the H. pylori infection rate is said to be inversely correlated with the prevalence of RE. 11 14 Eradication treatment of H. pylori results in elimination of inflammatory cell infiltration and may lead to improvement of atrophy. 6 It has been reported that elimination of inflammation and improvement of atrophy restore gastric acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…46 On the other hand, H. pylori infection is reported to be more frequently seen in low socioeconomic state. 47 As a consequent, low socioeconomic people might have more prevalence of H. pylori infection, which in turn, this infection might have protected them from GERD. So a further step in this study would be the evaluation of H. pylori infection in the GERD population of both high and low socioeconomic statuses in a comparative manner.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia including Japan, CagA‐ VacA‐positive virulent strains are common 12 , 13 . Such preponderance of CagA‐ and VacA‐positive strains and proinflammatory interleukin‐1 beta polymorphism are supposed to increase the risk of hypochlohydria and protects against the development of GORD in the Asian population 14 . In case of patients with corpus dominant gastritis, we should be wary of the development of new GORD; however, when it does develop, it is not so severe.…”
Section: Does H Pylori Eradication Develop New Gord?mentioning
confidence: 99%